Hubungan Lama Menjalani Hemodialisis dengan Status Gizi Pada Pasien Penyakit Ginjal Tahap Akhir yang Menjalani Hemdialisis di RSUD Provinsi NTB - Komang Adi Praja Semara Putra; I Gede Yasa Asmara; Rifana Cholidah (Unram Medical Journal, 2022)
Background: Chronic kidney disease is characterized by a decrease in kidney function for at least three months or more, a decrease in kidney function seen from a decrease in GFR < 60 ml/minute/1.73m2. The end stage of chronic kidney disease is known as end stage renal disease. Patients with end-stage renal disease require therapy to replace kidney function, one of the therapies that can be used is hemodialysis. Malnutrition is a condition that is often found in end-stage renal disease patients undergoing hemodialysis. Methods: This research is an observational analytic with a cross-sectional approach. Data were obtained from direct measurements and medical records of end stage kidney disease patients undergoing hemodialysis at the NTB Provincial Hospital with consecutive sampling technique. The analysis was carried out using the SPSS application. Results: In this study, there were 116 data that met the inclusion and exclusion criteria. Based on BMI, 13 of 116 samples were malnourished, 58 of 116 had normal BMI and 45 of 116 were overweight. Based on serum albumin, 33 of 116 had hypoalbuminemia and 83 of 116 had normal serum albumin. Conclusion: There was no relationship between duration of hemodialysis and body mass index of end-stage renal disease patients undergoing hemodialysis (p=1,000). There was a relationship between duration of hemodialysis and serum albumin in end-stage renal disease patients undergoing hemodialysis (p<0.00